Visual Loss Following Laproscopy with Contrast - Awan, Ayyaz Hussain (Pakistan Journal of Ophthalmology, 2007)
Case reports of serious operative complications resulting in permanent visual loss have appeared in the ophthalmology, anesthesialogy, and surgical literatures since the 1940’s. Perioperative ischemic optic neuropathy (POION), unilateral or bilateral, is a common cause of visual loss in non-ophthalmologic surgery. It is associated with anemia, hypotension, long duration of surgery, excessive hydration (causing intra-operative and immediate postoperative anemia), or a combination of these factors. Bilateral visual loss in the presence of normal pupillary light reflexes places the causative lesion posterior to the initial synapse between the retinal ganglion cells and cells of the LGN (lateral geniculate nuclei of the thalamus).